Challenges for universities lectures in Vietnam: English - nguyen, chau huu (Advances in Social Sciences Research Journal, 2020)
Vietnamese universities are under the process of changing training model to credit-based system from academic year system. It was acknowledged that the new model would increase workload and also diversify activities of lecturers in teaching activity. This paper firstly reviews teaching activities in the credit-based training approach. To explore the existing situation of the transition to credit-based system, the author uses a mixed method of survey research and interviews with lectures and students of a University in Vietnam. The study’s result shows that there were already an increase in workload and diversity in activities of lecturers. However, only a small number of teaching staff meets the demands of credit-based. Main reasons are resulted from the awareness of lecturers and students as well as the effects of the current outdated policies. This paper suggests several solutions to amend those policies that they are more practical and suitable for the teaching activities under the credit system.